Risk factors of bruxism in children and adolescents: A case-control study: Risk factors of bruxism in children and adolescents - Talebian , Ahmad; Sharif , Mohammad Reza; Gilasi , Hamid Reza; Ghafeli Bidgoli, Morteza; Masoudi Alavi, Negin (Iranian Journal of Child Neurology, 2023)
Objectives This study aimed to investigate the risk factors of bruxism in children and adolescents under 15 years old in Iran. Materials & Methods This case-control study was conducted in day clinics of Shahid Beheshti Hospital in 2020. Fifty children with bruxism in the case group and 50 without in the control group were compared to five risk factors, including intestinal parasites, sucking the fingers, biting objects, a family history of bruxism, and secondhand smoking (SHS). The statistical tests of smoking, odds ratio, and logistic regression were used for data analysis. Result: The mean age of the subjects was 10.6±3.2 and 10.8±2.9 years in the case and control groups, respectively. The bruxism showed significant relation with sucking the fingers, the family history of bruxism, and intestinal parasites. The SHS and biting objects showed no significant relation with bruxism. The logistic regression indicated that the study variables could explain the 22.6 to 30.1% of risk factors in bruxism. Conclusion Bruxism is a common disorder in children and adolescents. The intestinal parasites might be associated with bruxism. These infestations should be diagnosed and treated in children with bruxism.